Late Restenosis After Both First-Generation and Second-Generation Drug-Eluting Stent Implantations Occurs in Patients With Drug-Eluting Stent Restenosis. (December 2016) - Habara, Seiji; Kadota, Kazushige; Kuwayama, Akimune; Shimada, Takenobu; Ohya, Masanobu; Miura, Katsuya; Amano, Hidewo; Kubo, Shunsuke; Hyodo, Yusuke; Otsuru, Suguru; Tada, Takeshi; Tanaka, Hiroyuki; et al.
Abstract : Background—: There are currently inadequate data about whether late restenosis occurs after drug-eluting stent (DES) implantation in patients with DES restenosis. Methods and Results—: We collected data for 608 patients who received revascularization for DES restenosis between 2004 and 2012 and analyzed 688 lesions: 359 lesions treated with a first-generation DES (first DES) and 329 lesions treated with a second-generation DES (second DES). Two serial angiographic follow-ups were routinely planned for the patients (at 8 and 20 months after the procedure). Early follow-up angiography was performed for 620 lesions (90.1%), and recurrent restenosis occurred in 84 lesions (25.8%) in the first DES group and in 72 lesions (24.5%) in the second DES group ( P =0.78). Target lesion revascularization was performed for 69 lesions (21.2%) in the first DES group and for 48 lesions (16.3%) in the second DES group ( P =0.15). Late follow-up angiography was performed for 438 (87.1%) of the remaining 503 lesions (excluding target lesion revascularization lesions), and late restenosis was found in 35 lesions (15.8%) in the first DES group and in 28 lesions (14.7%) in the second DES group ( P =0.79). Nonfocal-type restenosis, percentage diameter stenosis after the procedure, previous stent size ⩽2.5 mm, and right coronary artery ostial lesion were independent predictors of early restenosis. Nonfocal-type restenosis, percentage diameter stenosis at early follow-up, and stent fracture were independent predictors of late restenosis. Conclusions—: Late restenosis occurs after both first DES implantation and second DES implantation for DES restenosis. Abstract : Supplemental Digital Content is available in the text.